n Oorsigtelike studie van metodes in Bantoe stamopvoeding - Van der Merwe, L. N., Louis Naude,1909- (Stellenbosch : Stellenbosch University, 2012)
Verhandeling (M.A.) -- Universiteit van Stellenbosch, 1938.